The Transformation of Nature in Art - Coomaraswamy, Ananda K., (Brill | Manohar Publishers & Distributors, 2024)
The history of art in the Indian subcontinent, indeed, is highly rich in its content, aesthetical value, and ornated in nature. The study of art is one of the most popular themes developed in the scholastic world in the twentieth century. But how the nature of art is studied is something unique in its approach. Coomaraswamy writes in this volume which covers the study of art and how its reconstruction was assessed in Indian contexts. Beginning with the history of art in the theoretical sense, it covers the art forms practiced in Asia such as Hindu, Buddhist, Chinese, Islamic, and others forms in the initial part of the volume. Interestingly, he also discusses the famous medieval German Catholic theologian Meister Eckhart (c.1328) in terms of art in a theoretical sense. This volume covers the perspective of Indian arts, the concept of paroksha, which is an important term applied in Buddhism, and abhasa, or appearance, which is used in Hindu philosophy. The author also compares the Indian concepts of art with Western philosophy and thought, which is the most interesting part. The concluding part of this book covers the origins and usage of images in Indian art.